Development of Argumentation Skills Test Instruments on Buffer Solutions in Daily Life - Lilla Pangestu Harwyandani; Suyono (Postgraduate, University of Mataram, 2023)
The purpose of this research is to develop a valid and reliable instrument for testing argumentation skills in buffer solutions in daily life. Argumentation skill test instruments are reviewed from theoretical validity (content and construct), empirical validity, and reliability. Development of argumentation skill test instruments using the ADDIE development model with stages: (1) analysis; (2) design; (3) development; (4) implementation; and (5) evaluation. This research was carried out until the initial implementation and then an evaluation was carried out. The argumentation skill test instrument that has been designed is then tested for theoretical validity through expert judgment involving three validators. The argumentation skill test instrument has criteria of theoretical validity if each statement has a mode â‰¥ 4 with valid categories. After being declared theoretically valid, argumentation skill test instruments are implemented to learners. The results of the argumentation skill test instrument are then analyzed to determine empirical validity and reliability. The results showed that the argumentation skill test instrument was declared theoretically valid where each statement had a mode of 5 with a very valid category. The test instrument is declared empirically valid where each question item has a consecutive calculated r value of 0.807; 0.879; 0.911; 0.911 is declared valid with r count > r table (0.468). The reliability of the argumentation skill test instrument of 0.876 is declared reliable with a r count > r table (0.468).